Gender context of sexual violence and HIV sexual risk behaviors among married women in Iringa Region, Tanzania - Tumaini M. Nyamhanga; Gasto Frumence (Taylor & Francis Group, 2014)
Background: There is a dearth of empirical research illuminating possible connections between gender imbalances and sexual violence among married women in Tanzania. There is a need to generate in-depth information on the connectivity between gender imbalances (asymmetrical resource ownership, sexual decision making, roles, and norms) and sexual violence plus associated HIV risky sexual behavior among married women. Design: This paper is based on a qualitative case study that involved use of focus group discussions (FGDs). A thematic analysis approach was used in analyzing the study findings. Results: The study findings are presented under the three structures of gender and power theory. On sexual division of labor, our study found that economic powerlessness exposes women to sexual violence. On sexual division of power, our study found that perception of the man as a more powerful partner in marriage is enhanced by the biased marriage arrangement and alcohol consumption. On cathexis, this study has revealed that because of societal norms and expectations regarding women's sexual behavior characterized by their sexual and emotional attachments to men, women find it hard to leave sexually abusive marriages. That is, because of societal expectations of obedience and compelled tolerance many married women do suffer in silence. They find themselves trapped in marriages that increase their risk of acquiring HIV. Conclusions: This study suggests that married women experience a sexual risk of acquiring HIV that results from non-consensual sex. That non-consensual sex is a function of gender imbalances - ranging from women's economic dependence on their husbands or partners to socioculturally rooted norms and expectations regarding women's sexual behavior. The HIV risk is especially heightened because masculine sexual norms encourage men [husbands/partners] to engage in unprotected intra- and extramarital sex. It is recommended that the Tanzania Commission for AIDS (TACAIDS) should address the gender dimensions of sexual violence in marriage.